2022
DOI: 10.3389/fonc.2022.991892
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of architectural distortion on digital breast tomosynthesis using radiomics and deep learning

Abstract: PurposeTo implement two Artificial Intelligence (AI) methods, radiomics and deep learning, to build diagnostic models for patients presenting with architectural distortion on Digital Breast Tomosynthesis (DBT) images.Materials and MethodsA total of 298 patients were identified from a retrospective review, and all of them had confirmed pathological diagnoses, 175 malignant and 123 benign. The BI-RADS scores of DBT were obtained from the radiology reports, classified into 2, 3, 4A, 4B, 4C, and 5. The architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…In a recently published paper (20), it was shown that the proposed radiomic model could help reduce unnecessary biopsies. In fact, especially in the presence of architectural distortion, DBT can detect some apparently benign lesions as suspicious because of its high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published paper (20), it was shown that the proposed radiomic model could help reduce unnecessary biopsies. In fact, especially in the presence of architectural distortion, DBT can detect some apparently benign lesions as suspicious because of its high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…28 This current review extracted and organized the data in tabular form and summarized the use of MG in the diagnosis of breast cancer (Table 1). 2,4,5,7,9,24,2979…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al. proposed two AI methods, radiomics and deep learning, to build diagnostic models for patients presenting with architectural distortion on Digital Breast Tomosynthesis (DBT) images ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rehman et al recently developed an automated computer-aided diagnostic system using computer vision and deep learning to predict breast cancer based on the architectural distortion on DM and reported great accuracy (16). Xiao et al proposed two AI methods, radiomics and deep learning, to build diagnostic models for patients presenting with architectural distortion on Digital Breast Tomosynthesis (DBT) images (17).…”
Section: Introductionmentioning
confidence: 99%